IFRS Implications of Covid 19 on Financial Reports: BIST 100 Analysis - izmirli ata, fatma; geyikçi, umut burak; yakupoğlu, lale (International Journal of Contemporary Economics and Administrative Sciences, 2022)
Companies which are one of the most important actors in the economic system are expected to be affected by the Covid-19 pandemic in many ways. This article investigates how these selected companies disclose financial information regarding the going concern, financial assets and revenue of company, impairment of tangible and intangible assets, stocks, provisions and liabilities and how the companies make accounting estimates to account for the uncertainty environment that has arisen because of pandemic on their financial reports. The purpose of this study is to determine the extent to which disclosures to be included in the financial reports of the companies in the Borsa Istanbul (BIST) 100 Index are affected by the Covid-19 pandemic in terms of Turkish Financial Reporting Standards (TFRS) and to make sectoral evaluations and comparisons. For this purpose, the data needed by the content analysis method from the financial reports of the 100 companies included in the BIST 100 Index for the years 2020 and 2021 in the Public Disclosure Platform (KAP) was obtained. The findings reveal that the companies took utmost care in disclosing information and impact of Covid-19 in their financial reports. It has been observed that the vast majority of companies have made disclosures about the impact of Covid-19 in at least one category in their financial reports. But these disclosures are quite limited, stereotypes are included in the disclosures and there are sectoral and inter-year differences.